A Co(OH)x nanolayer integrated planar WO3/Fe2O3 photoanode for efficient photoelectrochemical water splitting. Issue 8 (24th June 2019) - Ma, Wei; Wu, Xiaofeng; Huang, Keke; Wang, Meng; Fu, Rong; Chen, Huanwen; Feng, Shouhua
Abstract : A controllable planar Fe2 O3 /WO3 photoanode with an integrated Co(OH) x layer was prepared via an electrospray technique for enhanced PEC performance. Abstract : Hematite (α-Fe2 O3 ), with a suitable bandgap of 2.2 eV, is an ideal photoanode material to convert solar light into hydrogen fuel via photoelectrochemical (PEC) water splitting. However, poor charge separation efficiency in the bulk and slow oxygen evolution kinetics at the Fe2 O3 /electrolyte interface have restricted its PEC performance to date. Here, we designed and fabricated a nanostructured WO3 /Fe2 O3 thin film photoanode via an electrospray technique to promote bulk charge separation in Fe2 O3 . A Co(OH) x nanolayer was further coated onto the surface via a solution-based chemisorption method to improve the oxygen evolution kinetics. We found that the ratio of the deposition amount of WO3 to Fe2 O3 and the substrate temperature greatly influenced the PEC performance of the WO3 /Fe2 O3 photoanode. With an optimal deposition ratio of 1 : 1 and a substrate temperature of 400 °C, the WO3 /Fe2 O3 photoanode shows a photocurrent of 0.32 mA cm −2 at 1.23 V RHE, which is more than 30 times that of pure Fe2 O3 film. The photocurrent was further increased to 0.62 mA cm −2 after modification with a Co(OH) x nanolayer and an obvious cathodic onset potential shift of about 160 mV was observed. The results show that this enhanced photoactivity is attributed to simultaneously improved charge carrier separation efficiency at the WO3 /Fe2 O3 heterojunction interface and accelerated oxygen evolution kinetics at the surface.